Gender matters in cardiac rehabilitation and diabetes: Using Bourdieu's concepts. (March 2018) - Angus, Jan E.; Dale, Craig M.; Nielsen, Lisa Seto; Kramer-Kile, Marnie; Lapum, Jennifer; Pritlove, Cheryl; Abramson, Beth; Price, Jennifer A.; Marzolini, Susan; Oh, Paul; Clark, Alex
Abstract: Background: Habitual practices are challenged by chronic illness. Cardiac rehabilitation (CR) involves changes to habits of diet, activity and tobacco use, and although it is effective for people with diabetes and cardiovascular disease (CVD), some participants are reportedly less likely to complete programs and adopt new health related practices. Within the first three months of enrolling in CR, attrition rates are highest for women and for people with diabetes. Previous studies and reviews indicate that altering habits is very difficult, and the social significance of such change requires further study. Purpose: The purpose of the study was to use Bourdieu's concepts of habitus, capital and field to analyse the complexities of adopting new health practices within the first three months after enrolling in a CR program. We were particularly interested in gender issues. Methods: Thirty-two men and women with diabetes and CVD were each interviewed twice within the first three months of their enrolment in one of three CR programs in Toronto, Canada. Results: Attention to CR goals was not always the primary consideration for study participants. Instead, a central concern was to restore social dignity within other fields of activity, including family, friendships, and employment. Thus, study participants evolved improvised tactical approaches that combined both physical and social rehabilitation. These improvised tactics were socially embedded and blended new cultural capital with existing (often gendered) cultural capital and included: concealment, mobilizing cooperation, re-positioning, and push-back . Conclusions: Our findings suggest that success in CR requires certain baseline levels of capital – including embodied, often gendered, cultural capital – and that efforts to follow CR recommendations may alter social positioning. Highlights: Bourdieu's concepts illuminated the complexities of Cardiac rehabilitation (CR). Study participants did not always keep CR goals as the primary consideration. Rather, they acted to restore social standing within other fields of activity. Improvised tactics were socially embedded and often gendered. Success in CR requires nuanced understanding of such factors.